Wednesday

October 22, 2014

October 22, 2014

Posted by **Anonymous** on Thursday, July 6, 2006 at 7:43pm.

What is F o G and Domain

Okay, we are given f and g as functions of x. To compose a function means to use one function, g in this case, as the argument of the other, f in this case. Thus we want f o g = f(g(x))

With f(x) = 2x-4 and g(x) = x^2 + 5x, f o g becomes f(x^2 +5x)= 2(x^2 +5x) - 4.

What we do is substitue the equation for g into each place the argument of f occurs. I'll let you determine the domain.

Incidentally, it might be a little easier to grasp composite functions if you don't use the same variable in both functions. Example: suppose f= 2x-4, as you have above and g is a function of t, say g(t)=3t-1. Then in this case f o g = f(g(t)). To evaluate this, we put g(t) in place of the x in the equation 2x-4, so f o g = 2g(t)-4. We now substitute the equation for g(t) to get f o g = 2(3t-1)-4, which we would simplify to f(g(t))=6(t-1) for this example.

- composite functions -
**JOe**, Sunday, January 13, 2013 at 8:14pmSince the the domain of the inner function belongs to real numbers(a polynomial) and the new function is also a polynomial...therefore the domain is all real numbers.

**Answer this Question**

**Related Questions**

Functions - consider the functions g(x)=(4-x^2)^0.5 and h(x)=(x^2)-5. find the ...

functions - For each problem, construct two composite functions, . Evaluate each...

Composite Functions - Find the composite functions for the given functions. (6 ...

algebra functions - construct two composite functions, Evaluate each composite ...

college algebra - Let f(x) = square root (x + 2) and g(x) = x^2 − 2. ...

Calculus - Find the sum and difference functions f + g and f – g for the ...

Calculus - Math questions, please help me? :(? Find the composite functions f o ...

algebra functions - can someone please check my answer For each problem, ...

algebra functions check my answer - For each problem, construct two composite ...

college algebra - Let f(x) = 1/x − 2 and g(x) = 1/x − 3 . Determine ...